Strain‐Specific Impact of Fusobacterium nucleatum on Neutrophil Function. Issue 4 (1st April 2017) - Kurgan, Şivge; Kansal, Shevali; Nguyen, Daniel; Stephens, Danielle; Koroneos, Yannis; Hasturk, Hatice; Van Dyke, Thomas E.; Kantarci, Alpdogan
Abstract : Background: Neutrophil function is critical for initiation and progression of infecto‐inflammatory diseases. Key quorum‐sensing plaque bacteria, such as Fusobacterium nucleatum, act as bridging species between early and late colonizer pathogens, such as Porphyromonas gingivalis, as the biofilm ages and periodontal inflammation increases. This study is designed to determine impact of different F. nucleatum strains on neutrophil function. Methods: Cells of human promyelocytic leukemia cell line‐60 were differentiated into neutrophil‐like cells and cultured with F. nucleatum strains of subspecies (ssp.) nucleatum ATCC 25586, ssp. polymorphum ATCC 10953, and ssp. vincentii ATCC 49256. Neutrophil phagocytosis of F. nucleatum strains and neutrophil apoptosis were analyzed by flow cytometry. Superoxide generation was measured by cytochrome C reduction in the presence and absence of N‐formyl‐L‐methionyl‐L‐leucyl‐L‐phenylalanine (fMLP) (1 μM) stimulation. Proinflammatory cytokine release was determined after 2, 6, and 24 hours of culture in the presence/absence of different F. nucleatum strains. Expression of Toll‐like receptor (TLR)2, TLR4, and nuclear factor (NF)‐kappa B mRNA levels were analyzed using real‐time quantitative polymerase chain reaction. Each experiment was repeated at least three times in triplicate. Data were analyzed using analysis of variance followed by post hoc Bonferroni correction. Results: All strains of F. nucleatum significantly increased phagocytic capacity of neutrophils. Neutrophil phagocytosis of F. nucleatum ssp. polymorphum was significantly greater than that of F. nucleatum ssp. vincentii and ssp. nucleatum ( P <0.001). F. nucleatum ssp. nucleatum and ssp. polymorphum significantly blocked fMLP‐induced superoxide generation ( P <0.001). Although F. nucleatum vincentii also reduced superoxide generation (25%), the impact was not as strong as that of ssp. nucleatum (83%) and ssp. polymorphum (100%). All F. nucleatum strains stimulated significant increase in neutrophil apoptosis compared with control ( P <0.001) and significantly increased expression of NF‐κB mRNA in neutrophils ( P <0.05). Levels of interleukin‐8 and tumor necrosis factor‐α produced by neutrophils were significantly increased in all F. nucleatum groups compared with control ( P <0.001). Conclusions: These findings suggest that different strains of F. nucleatum impact neutrophil function in different ways. Two of three subspecies blocked neutrophil superoxide generation in response to a secondary stimulus, preventing oxidative killing by neutrophils. The direct role of bridging species in pathogenesis of periodontitis may be greater than previously suspected in which they create a favorable environment for pathogenic transition of the dental ecosystem.